Upaya Kepala Sekolah Untuk Meningkatkan Profesionalisme Komunitas Belajar Di Lembaga PAUD - Enik Susiana; Imron Arifin; Yudithia Dian Putra (Universitas Muhammadiyah Metro, 2025)
The principal plays a very strategic role in fostering and improving teacher professionalism. The principal is responsible for creating collaboration between teachers, thus creating an atmosphere of mutual learning. The principal's change efforts include establishing a professional learning community at school. This study aims to analyze the principal's efforts in improving the professionalism of the learning community. The research used a qualitative approach with a case study type; data were collected through direct observation, in-depth interviews, and documentation. The research location was Mutiaran Bunda II Kindergarten, Madiun Regency. The research subjects were six teachers. The results showed that the principal's efforts in improving the professionalism of the learning community were: first, by effectively utilizing school resources, namely teachers, the learning environment, and infrastructure; and second, encouraging continuous training and development for teachers to broaden their knowledge and teaching insights. Third, focusing on improving learning by reflecting on learning for student-centered education, and fourth, sharing knowledge and experiences with teacher communities in other schools as part of developing teachers' social competence. The professional learning community is an effort in which teachers work collectively to improve the quality of education. The role of the principal is not only as an administrative manager, but also as an instructional leader who has a direct influence on increasing the professional capacity of teachers